Effects of Ginkgolide A on Okadaic Acid-induced Tau Hyperphosphorylation and the PI3K-Akt Signaling Pathway in N2a Cells - Chen, Yan; Wang, Cui; Hu, Meili; Pan, Jian; Chen, Jianhua; Duan, Peilu; Zhai, Tianlong; Ding, Jingna; Xu, Cunji (Planta Medica, 2012)
Alzheimerʼs disease is the most common form of dementia leading to the irreversible loss of neurons, and Tau hyperphosphorylation has an important role in the pathology of Alzheimerʼs disease. Ginkgolide A is one of the active components of Ginkgo biloba extracts which has been proven to have neuroprotective effects, but the effect of ginkgolide A on Tau hyperphosphorylation has not yet been reported. In this study, the effects of ginkgolide A on cell viability, Tau hyperphosphorylation, and the PI3K-Akt signaling pathway in N2a cell lines were explored, and methods such as the MTT assay, ELISA, and Western blots techniques were used. The results showed that ginkgolide A could increase cell viability and suppress the phosphorylation level of Tau in cell lysates, meanwhile, GSK3β was inhibited with phosphorylation at Ser9. Moreover, treatment of the cells with ginkgolide A promoted phosphorylation of PI3K and Akt, suggesting that the activation of the PI3K-Akt signaling pathway may be the mechanism for ginkgolide A to prevent the intracellular accumulation of p-Tau induced by okadaic acid and to protect the cells from Tau hyperphosphorylation-related toxicity.
Keywords: ginkgolide A; Tau hyperphosphorylation; N2a cells; PI3K-Akt signaling pathway